Antibacterial Silver-Conjugated Magnetic Nanoparticles: Design, Synthesis and Bactericidal Effect - Shatan, Anastasiia B; Venclíková, Kristýna; Zasońska, Beata A; Patsula, Vitalii; Pop-Georgievski, Ognen; Petrovský, Eduard; Horák, Daniel (Pharmaceutical research, 2019)
PURPOSE: The aim was to design and thoroughly characterize monodisperse Fe3O4@SiO2-Ag nanoparticles with strong antibacterial properties, which makes them a candidate for targeting bacterial infections. METHODS: The monodisperse Fe3O4 nanoparticles were prepared by oleic acid-stabilized thermal decomposition of Fe(III) oleate; the particles were coated with silica shell using a water-in-oil reverse microemulsion, involving hydrolysis and condensation of tetramethyl orthosilicate. Resulting Fe3O4@SiO2 particles were modified by (3-mercaptopropyl)trimethoxysilane to introduce 1.1 mmol SH/g. Finally, the Fe3O4@SiO2-SH nanoparticles were decorated with silver nanoclusters formed by reduction of silver nitrate with NaBH4. The particles were analyzed by FTIR, X-ray photoelectron and atomic absorption spectroscopy, dynamic light scattering and vibrating sample magnetometry. The antibacterial activity of the Fe3O4@SiO2 and Fe3O4@SiO2-Ag nanoparticles was tested against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria cultivated on Luria agar plates or in Luria broth. RESULTS: The superparamagnetic Fe3O4@SiO2-Ag nanoparticles (21 nm in diameter; saturation magnetization 26 A∙m2/kg) were successfully obtained and characterized. Inhibitory and toxic effects against bacteria were documented by incubation of the Fe3O4@SiO2-Ag nanoparticles with Staphylococcus aureus and Escherichia coli. CONCLUSIONS: The combination of magnetic properties together with bactericidal effects is suitable for the disinfection of medical instruments, water purification, food packaging, etc.
Keywords: thiol-functionalization; povrchové vlastnosti; Organosilicon Compounds; Silicon Dioxide; Silver; Particle Size; Staphylococcus aureus; silany; organické sloučeniny křemíku; antibakteriální látky; Oleic Acid; Escherichia coli; Magnetite Nanoparticles; silica shell; magnetické nanočástice; Anti-Bacterial Agents; velikost částic; Surface Properties; oxid křemičitý; Silanes; stříbro; magnetic nanoparticles; antibacterial activity; kyselina olejová